Audit Manajemen Atas Fungsi Sumber Daya Manusia Pada Dinas Peternakan Dan Kesehatan Hewan (DPKH) Provinsi Kalimantan Timur: Audit atas Fungsi Sumber Daya Manusia Pada Dinas Peternakan dan Kesehatan Hewan (DPKH) Provinsi Kalimantan Timur - Camelia Verahastuti; H.Sunarto; Herlina, Tri Dara (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Audit of the human resources function at the Department of Animal Husbandry and Animal Health (DPKH) of East Kalimantan province, under the guidance of Mrs. Camelia Verahastuti as supervisor I and Mr. H. Sunarto as supervisor II. This study aims to determine and analyze the effectiveness of Human Resource function management audit in the program of human resource training and development activities at the Department of Animal Husbandry and Animal Health (DPKH) of East Kalimantan province. The method used is descriptive qualitative. The research method used is a qualitative descriptive analysis that describes the Audit of Human Resources Management and ICQ (Internal Control questionnaires). The hypothesis put forward is the Audit of Human Resource Management in the program of training and career development activities at the Department of Animal Husbandry and Animal Health (DPKH) East Kalimantan is less effective.. The analysis tool used is the calculation to determine the percentage of the score from the results of the questionnaire using the Dean j. Champion and the reporting phase using audit working paper (KKA) used to collect sufficient and competent evidence conducted with the development of findings to find the relationship between one finding and another in testing problems related to audit objectives. He results showed that the implementation of the Audit on the function of human resources at the Department of Animal Husbandry and Animal Health (DPKH) of East Kalimantan province training and Human Resources Development Activity program based on the calculation of the percentage score from the questionnaire has been running effectively. Keywords: Audit function of Human Resources, questionnaires, audit working papers.